Marxist Feminism: An Analysis on Class Structure and Position of Women in Malayalam movie -“Chemmeen” - Ann Rose Davis , (The Creative Launcher, 2021)
The Malayalam film industry, prominently known as “Mollywood,” is one of the fast-changing faces in Indian cinema. This paper tries to examine one of the Malayalam movies, Chemeen, through the lens of Marxist Feminism. The primary text chosen for the study is the movie, Chemeen, an adaptation of Thakazhi Sivasankara Pillai’s novel with the same name. The story revolves around the lives of Karuthamma and Pareekutt, lovers whose life cannot be led together because of the strong influence of caste and class in their society. This is one of the liberal texts in Malayalam Literature narrating the Kerala fishing community’s lives, customs, traditions, and beliefs. The research paper’s primary focus will be on society’s hierarchy through the reflection of Mollywood cinema, the stereotyping of certain characters based on their class and caste, the aftermath of marriage, and the domineering male-centric society female fellowships through deities.